Effects of CTL with Simeli on Cognitive Learning Outcomes, and Inter-Intrapersonal Skills (Universitas Negeri Semarang, 2019)
This study aims to analyze the influence of the Contextual Teaching and Learning (CTL) model with Simeli media on cognitive learning outcomes and inter-intrapersonal skills of Grade VI students on science subjects electrical energy materials. The research design used is quantitative quasi-experiment. The population of the research was Grade VI Elementary School students in Jumo District. Sampling technique by purposive sampling, obtained from students as many as 22 from Public Elementary School 1 Jombor, 25 from Public Elementary School Giyono, and 23 from Public Elementary School 1 Kertosari. Research data on cognitive learning outcomes and inter-intrapersonal skills were obtained from tests and observations. Data analysis using Anova test with the help of SPSS 25. The results obtained by an average of cognitive learning outcomes of experimental class I was 92.50, experimental class II was 92.72, and control class was 70.13. The average inter-intrapersonal skills of experimental class I was 82.41, experimental class II was 81.48, and control class was 73.13. These data indicate that the average cognitive learning outcomes and inter-intrapersonal skills of the experimental class are higher than that of the control class. Anova test on cognitive learning outcomes showed Fvalue = 116.210 with a significant value of 0.000 < 0.05, while the Anova test results on inter-intrapersonal skills showed Fvalue = 13.088 with a significant value of 0.000 < 0.05. The conclusion of the CTL model with simile media affects improving cognitive learning outcomes, and inter-intrapersonal skills of Grade VI students on science subjects electric energy material.